Highly efficient and stable planar heterojunction solar cell based on sputtered and post-selenized Sb2Se3 thin film. (October 2019) - Tang, Rong; Zheng, Zhuang-Hao; Su, Zheng-Hua; Li, Xue-Jin; Wei, Ya-Dong; Zhang, Xiang-Hua; Fu, Yong-Qing; Luo, Jing-Ting; Fan, Ping; Liang, Guang-Xing
Abstract: Antimony selenide (Sb2 Se3 ) is regarded as one of the key alternative absorber materials for conventional thin film solar cells due to its excellent optical and electrical properties. Here, we proposed a Sb2 Se3 thin film solar cell fabricated using a two-step process magnetron sputtering followed by a post-selenization treatment, which enabled us to optimize the best quality of both the Sb2 Se3 thin film and the Sb2 Se3 /CdS heterojunction interface. By tuning the selenization parameters, a Sb2 Se3 thin film solar cell with high efficiency of 6.06% was achieved, the highest reported power conversion efficiency of sputtered Sb2 Se3 planar heterojunction solar cells. Moreover, our device presented an outstanding open circuit voltage ( V OC ) of 494 mV which is superior to those reported Sb2 Se3 solar cells. State and density of defects showed that proper selenization temperature could effectively passivate deep defects for the films and thus improve the device performance. Graphical abstract: Image 1 Highlights: A promising sputtered and post-selenized Sb2 Se3 thin film was present. Orientation, morphology, composition and defect passivation was depending on the post-selenized temperature. Highest PCE of 6.06% for sputtered Sb2 Se3 planar heterojunction solar cells achieved.